2005
DOI: 10.1300/j116v09n01_01
|View full text |Cite
|
Sign up to set email alerts
|

Online Sheet Music Projects and Metadata from a Public Service Perspective

Abstract: As historic sheet music collections enter the public domain, they are becoming increasingly popular as content for digital library projects. This newfound plethora of sheet music citations and images online has generated many patron inquiries. Patrons often cannot, or do not, distinguish sources that are found in the online catalog from those found through a Google search. To them the results are all "on the web." It is oftentimes the Reference Librarian's job to redirect the patron to the correct citation or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 2 publications
0
9
0
Order By: Relevance
“…Factor 5 -the presence of links to audio versions -did not have a positive influence on item selection at all. Research has shown that most users of music collections, physical or digital, are doing known item searches (Riley and Dalmau, 2007;Dougan, 2004). This may explain why the addition of audio links did not increase page views for those items.…”
Section: Conclusion and Next Stepsmentioning
confidence: 99%
See 1 more Smart Citation
“…Factor 5 -the presence of links to audio versions -did not have a positive influence on item selection at all. Research has shown that most users of music collections, physical or digital, are doing known item searches (Riley and Dalmau, 2007;Dougan, 2004). This may explain why the addition of audio links did not increase page views for those items.…”
Section: Conclusion and Next Stepsmentioning
confidence: 99%
“…Ideally, users of any digital collection will find their way to the collection, find what they need, remain there to browse/search for other items and return to the collection later. An easy-to-use interface for both searching and browsing is as important for music collections as it is for other types of digital collections (Wheeler and Venetis, 2005;Riley and Dalmau, 2007;Dougan, 2004;Kulik, 2010;Inskip et al, 2008;Dubnjakovic, 2009). Metadata for music collections should include alternative titles and text versions of lyrics, as users are frequently unfamiliar with the official title of a work and often use a portion of the lyrics when doing a title search (Riley and Dalmau, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Due to the large amount of information on the Internet, Dougan (2006) points out that queries on search bars can produce an equally large number of results, even with consolidated tools. In addition, netizens often find it difficult to discern between different types of searches, such as a library catalogue, a Google search, the free web or the deep web itself, because if the information has been located via the browser on the Internet, they automatically assume that it is only available on the Web, without further understanding.…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, musical scores can be considered as an example of a document and information object, as they go through representation processes in order to be retrieved and accessed. When talking about location, Dougan (2006) adds that they are mostly affiliated to universities or cultural institutions, especially historical scores that have not been made available by netizens. Such an affiliation allows the score and its history to be preserved.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation